2013
DOI: 10.7860/jcdr/2013/5352.2876
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to Anti-Diabetic Drugs: Observations from the Diabetic Clinic of a Medical College in Kolkata, India

Abstract: It can be concluded that the compliance to anti-diabetic drugs was quite poor among the participants. Increasing age, the male sex, illiteracy, a low monthly income and a longer duration of diabetes were significantly associated with the non compliance. A more concerning fact was the significant association of the non-compliance with the types of drug regimens and a lack of knowledge on the complications of diabetes, which emphasized the role of a repeated patient education regarding the basic aspects of diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
71
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 12 publications
21
71
9
Order By: Relevance
“…Conversely, in a study done by Shuvankar Mukherjee et al reported compliance decreased significantly with increasing age, among males, illiterates and those with poor per capita monthly income. 11 This study showed that 58.5% of non-compliant patients had associated chronic diseases and there is statistically significant association which is in accordance with study done by Lizbeth Hernandez-Ronquillo et al in Mexico. 12 A statistically significant association was found between non-compliance and financial problems to get medicines in the current study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Conversely, in a study done by Shuvankar Mukherjee et al reported compliance decreased significantly with increasing age, among males, illiterates and those with poor per capita monthly income. 11 This study showed that 58.5% of non-compliant patients had associated chronic diseases and there is statistically significant association which is in accordance with study done by Lizbeth Hernandez-Ronquillo et al in Mexico. 12 A statistically significant association was found between non-compliance and financial problems to get medicines in the current study.…”
Section: Discussionsupporting
confidence: 81%
“…7 Similar kind of association between non-compliance and financial problems to buy medications prescribed were reported in some other studies too. 11,13,14 This may be due to the fact that many of the anti-diabetic drugs are expensive and non-availability of all the drugs in the government sector.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Fredrick et.al 10 , medication adherence was found to be 71.7% and Shams et.al 11 study found it to be 61%. In our study, patients on Insulin constituted 28.7% of the total while in a study by Shuvankar et al 12 , it was as high as 52.1%. Only 4% of the patients are on Insulin monotherapy, which is comparable with other studies.…”
Section: Discussionmentioning
confidence: 81%
“…The findings are comparable to several Indian studies documenting poor medication adherence in diabetic patients. 21,28,29,38 Sharma et al 21 documented that only 16.6% of the patients were adhering to the prescribed antidiabetic drugs, and majority often forgot to take antidiabetic medications. Nonadherence was high and significantly (p < 0.001) associated with frequent dosing and multiple drugs in the prescription, especially attributed to the "forgetfulness" in the older/occupationally retired age groups.…”
Section: Discussionmentioning
confidence: 99%